Inflammatory profile in X‐linked adrenoleukodystrophy patients: Understanding disease progression. Issue 1 (23rd August 2017) - Marchetti, Desirèe Padilha; Donida, Bruna; Jacques, Carlos Eduardo; Deon, Marion; Hauschild, Tatiane Cristina; Koehler‐Santos, Patricia; de Moura Coelho, Daniella; Coitinho, Adriana Simon; Jardim, Laura Bannach; Vargas, Carmen Regla
Abstract: X‐linked adrenoleukodystrophy (X‐ALD) is an inherited disease characterized by progressive inflammatory demyelization in the brain, adrenal insufficiency, and an abnormal accumulation of very long chain fatty acids (VLCFA) in tissue and body fluids. Considering that inflammation might be involved in pathophysiology of X‐ALD, we aimed to investigate pro‐ and anti‐inflammatory cytokines in plasma from three different male phenotypes (CCER, AMN, and asymptomatic individuals). Our results showed that asymptomatic patients presented increased levels of pro‐inflammatory cytokines IL‐1β, IL‐2, IL‐8, and TNF‐α and the last one was also higher in AMN phenotype. Besides, asymptomatic patients presented higher levels of anti‐inflammatory cytokines IL‐4 and IL‐10. AMN patients presented higher levels of IL‐2, IL‐5, and IL‐4. We might hypothesize that inflammation in X‐ALD is related to plasmatic VLCFA concentration, since there were positive correlations between C26:0 plasmatic levels and pro‐inflammatory cytokines in asymptomatic and AMN patients and negative correlation between anti‐inflammatory cytokine and C24:0/C22:0 ratio in AMN patients. The present work yields experimental evidence that there is an inflammatory imbalance associated Th1, (IL‐2, IL‐6, and IFN‐γ), Th2 (IL‐4 and IL‐10), and macrophages response (TNF‐α and IL‐1β) in the periphery of asymptomatic and AMN patients, and there is correlation between VLCFA plasmatic levels and inflammatory mediators in X‐ALD. Furthermore, we might also speculate that the increase of plasmatic cytokines in asymptomatic patients could be considered an early biomarker of brain damage and maybe also a predictor of disease progression. Abstract : Asymptomatic patients for X‐ALD presented high levels of cytokines compared to cerebral phenotype. Cytokines might be considered a biomarker for earlier brain damage in this disease.